Seed treatment with niacin or thiamin provides bean plant development and productivity - Vendruscolo, Eduardo Pradi; Rodrigues, Aliny Heloísa Alcântara; Martins, Angélica Pires Batista; Campos, Luiz Fernandes Cardoso; Seleguini, Alexsander (Revista de Ciências Agroveterinárias, 2018)
Bean crop has socioeconomic importance in all Brazilian regions, but its cultivation is still related to rudimentary techniques that affect productivity. The use of vitamins contributes to the improvement of the vegetative and reproductive development, improving the plants physiological conditions. The objective of this study was to evaluate the effects of the application of niacin or thiamine on the vegetative and productive development characteristics of bean, in pots. Two experiments were conducted, on both the treatments were defined by the application of Niacin or Thiamin in five different dosages (0.00, 5.00, 10.00, 15.00 and 20.00 mg kg-1) along with fungicide in seed treatment. Variables related to seedling emergence, vegetative development and grain production were evaluated. It was verified, for bean plants (cv. BRS Estilo), that seed pre-treatment with niacin decreases seedling emergence time (20.31%) and stimulated the development of trefoils (16.21%), while the application of thiamine increased seedling emergence at the first count (287.52%), stimulated the emergence rate (36.72%) and the emergence speed index (65.76%), decreased the mean time of emergence (19.03) and increased the number of pods per plant (116.28%), grains per plant (122.28%) and grain productivity (127.50%), compared to the control treatment.